Pengaruh Tingkat Kedalaman Penyimpanan dengan Menggunakan Media Simpan Pasir terhadap Umur Simpan Buah Tomat (Solanum lycopersicum) - Alvin Restian; Tamrin Tamrin; Sri Waluyo; Sapto Kuncoro (Jurnal Agricultural Biosystem Engineering, 2022)
Tomatoes are agricultural commodities that are very susceptible to post-harvest damage. The main problem experienced by farmers is to maintain the shelf life of tomatoes which are not durable and are easily damaged by physical and chemical damage. The purpose of this study was to determine the effect of the depth of the storage pit from the surface of the sand on the shelf life of tomatoes during storage. This study uses a Single Factor Completely Randomized Design (CRD) which has a different depth factor (20 cm, 30 cm, and 40 cm). The observations made were three observations, the first observation was the characteristics of the sand, the second observation was the measurement of temperature in the storage environment, and the third observation was the observation of the fruit characteristics consisting of changes in weight loss, hardness, water content, total dissolved solids and color. The experiment was repeated three times. The results showed that the depth level had a significant effect on fruit color during storage, but the depth level had no significant effect on weight loss, hardness, water content, and total dissolved solids. The shelf life has a significant effect on hardness, moisture content, and total dissolved solids. The shelf life of tomatoes at a depth of 20 cm, 30 cm, and 40 cm is up to 18 days while the shelf life at room temperature which is no longer suitable for sale, starting on the 12th day because the tomatoes have changed color to dark red and the hardness of the fruit has decreased to become soft or criticized with a hardness value of 02,1 kg.mm/s. Keywords: Depth Level, Shelf Life, Tomato.